The Varian of Jargon Language in Palu Central-Sulawesi (The Study of Morphological Science) - Qarni, Wais (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
This research-based paper presents the investigation on Morphological process of tabale language in Palu Central-Sulawesi. Therefore, the aims of this study are to describe the use of Tabale language in Palu Perumnas Balaroa and to introduce the uniqueness of the jargon (Tabale language) to the public.This study used descriptive qualitative method. This research also used Remembering method to collect the data, because the researcher himself was the native of this jargon language, the other method which was used was agih method to analyze the data. This research result showed the public about the uniqueness of morphological process in Bahasatabale such as (1. Ma-kanbecomeKan-ma, 2. Ti-durbecomeDur-ti, 3. Se-le-sai become Le-sai-se, 4. Me-nung-gu become Ba-gu-tung, 5.Ter-ti-dur become Ta-dur-ti).